Development of an open-source and low-cost robotic arm based on STM32 microcontroller for promoting STEM education - Mohd Asri, Fatin Atirah; Ayob, Mohammad Afif; Rohaziat, Nurasyeera; Rahman, Hisyam Abdul; Rahman, Khairul Azlan A.; Ayob, Mohd Erdi (2023)
As a key component of Industry 4.0, robotics is acquiring traction in classrooms around the world. Robotics initiatives may stimulate students' interest in STEM (Science, Technology, Engineering, and Mathematics) subjects. Therefore, it is essential to translate theoretical information into tangible prototypes and study robotics using physical models. Most schools cannot afford to provide students with sufficient opportunities to work with robots due to the expense of robotics. This study aims to promote STEM education by describing the development of a free, open-source robot joint with three degrees of freedom (DOF). The control algorithm for a 3D-printed MK2 robot arm was programmed with an STM32 microcontroller. The robot has a servo-powered arm that has a gripper on the end-effector. A joystick can be used to control the movement of any mechanical joint. The forward kinematic has also been constructed and validated in a simulation-based environment in MATLAB and SolidWorks. The developed kinematics algorithm showed precise Denavit-Hartenberg (DH) characteristics with high accuracy with the worst-case scenario for the kinematic computation error contributes to only 0.26% or 0.0702mm of the end-effector position.